САБЗАВОТ УРУҒЛАРИНИ ЭКИШГА ТАЙЁРЛАНГАН ДАЛА ТУПРОҒИНИНГ ФИЗИК-МЕХАНИК ХОССАЛАРИНИ ЎРГАНИШ - Эшдавлатов, А.Э.; Хамидов, Н.М. (SCIENCE and SOCIETY, 2021)
This article presents the results of research on the study of physical and mechanical properties of field soil prepared for sowing seeds of vegetable crops in the experimental farm of the Research Institute of Agricultural Mechanization.
Keywords: physical and mechanical properties of soil; angle of repose; working body; construction; factors; vegetable; sowing seeds; soil layer; agro technical requirements